Semiconductor Fe-doped SrTiO3-δ perovskite electrolyte for low-temperature solid oxide fuel cell (LT-SOFC) operating below 520 °C. (21st May 2020) - Shah, M.A.K. Yousaf; Rauf, Sajid; Mushtaq, Naveed; Tayyab, Zuhra; Ali, Nasir; Yousaf, Muhammad; Xing, Yueming; Akbar, Muhammad; Lund, Peter D.; Yang, Chang Ping; Zhu, Bin; Asghar, Muhammad Imran
Abstract: High-temperature operation of solid oxide fuel cells causes several degradation and material issues. Lowering the operating temperature results in reduced fuel cell performance primarily due to the limited ionic conductivity of the electrolyte. Here we introduce the Fe-doped SrTiO3-δ (SFT) pure perovskite material as an electrolyte, which shows good ionic conduction even at lower temperatures, but has low electronic conduction avoiding short-circuiting. Fuel cell fabricated using this electrolyte exhibits a maximum power density of 540 mW/cm 2 at 520 °C with Ni-NCAL electrodes. It was found that the Fe-doping into the SrTiO3-δ facilitates the creation of oxygen vacancies enhancing ionic conductivity and transport of oxygen ions. Such high performance can be attributed to band-bending at the interface of electrolyte/electrode, which suppresses electron flow, but enhances ionic flow. Highlights: SrFe0.2, 0.3TiO3-δ (SFT) single-phase semiconductor utilized as an electrolyte in SOFC. SrFexTi1-xO3-ä(x = 0.3) has revealed high ionic conductivity of 0.17 S/cm at 520 °C. Fuel-cell based SrFexTi1-xO3-δ(x = 0.3) electrolyte has demonstrated impressive performance of 540 mW/cm2 at 520 °C.